2022
DOI: 10.1038/s41598-022-13948-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mechanisms of peritoneal metastasis in gastric adenocarcinoma using a novel ex vivo peritoneal explant model

Abstract: Gastric adenocarcinoma, commonly known as stomach cancer, has a predilection for metastasis to the peritoneum, which portends limited survival. The peritoneal metastatic cascade remains poorly understood, and existing models fail to recapitulate key elements of the interaction between cancer cells and the peritoneal layer. To explore the underlying cellular and molecular mechanisms of peritoneal metastasis, we developed an ex vivo human peritoneal explant model. Fresh peritoneal tissue samples were suspended, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Importantly, when ALCAM were knocked down from both cancer cells and mesothelial cells, the interaction between the two cell types were greatly reduced compared to an individual knocking down, further supporting the role of ALCAM in both "seed" and "soil" receptors during the process of metastasis. This finding on ALCAM has a similar echo to a recent study by Ng et al [49] who reported that E-cadherin may have a similar property in an ex vivo gastric cancer model. Similar suggestions were indicated in the peritoneal metastasis from pancreatic cancer, although experimental data are yet to come [50].…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, when ALCAM were knocked down from both cancer cells and mesothelial cells, the interaction between the two cell types were greatly reduced compared to an individual knocking down, further supporting the role of ALCAM in both "seed" and "soil" receptors during the process of metastasis. This finding on ALCAM has a similar echo to a recent study by Ng et al [49] who reported that E-cadherin may have a similar property in an ex vivo gastric cancer model. Similar suggestions were indicated in the peritoneal metastasis from pancreatic cancer, although experimental data are yet to come [50].…”
Section: Discussionsupporting
confidence: 88%
“…In short, tumor metastasis involves interaction between the primary tumor and the local microenvironment of the new metastatic site. Therefore, by providing various cytokines that promote tumor invasion and metastasis, tumors promote peritoneal changes to facilitate the adhesion of shed tumor cells to the peritoneum, which is an important basis for the occurrence of GC peritoneal metastasis [ 6 , 7 ]. This process involves interaction between the primary tumor and peritoneal mesenchymal cells and the extracellular matrix (ECM) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The omentum is the preferred early site of peritoneal metastasis of cancer cells, including gastric, pancreatic, and high‐grade serous ovarian cancer [ 17 , 18 , 19 ]. Milky spots (MS), lymphoid tissues most frequently observed in the omentum and mesentery, comprise B, T, and natural killer cells, along with MΦs, and other immune‐progenitor cells and play an essential role in cancer metastasis colonization [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%